Impact De L’exercice Aerobie Combine Au Jeune Du Ramadan Sur Quelques Indices Physiques Et Biologiques Lies A La Sante Chez Les Femmes - Said Aissa , Kheiifa; taileb, sabrina (Journal of Sport Science Technology and Physical Activities, 2019)
This study aims to analyse the impact of aerobic exercise combined with Ramadan fasting on some physical and biological indices related to health in women (25-35 years). The sample consists of 21 women, divided into two groups. Only the experimental group followed a moderate exercise program during the month of Ramadan. On the one hand, we note no significant differences between the health-related fitness index test periods in the control group (CG), at which women only fasted. However, various improvements of his own indices have been recorded within the Experimental Group (EG). On the other hand, we note no significant difference between the three sampling periods on health-related biological indexes at the CG. But in the EG we has a significant results for blood glucose and cholesterol, and not significant for triglyceride and lactate. At the end. We put these differences precisely in the intervention for use in this study. As a result, we can conclude that moderate physical activity during the month of Ramadan can help slight improvements in some health-related physical and biological indices.